LC-Q-TOF/MS based identification and in silico verification of ACE-inhibitory peptides in Giresun (Turkey) hazelnut cakes - (:unkn) unknown (SPRINGER, 2021)
Hazelnut (Corylus avellana L.) cakes represent are a rich source of proteins. In an effort to valorize industrially cold-pressed hazelnut cakes, angiotensin-converting enzyme (ACE) inhibitory characteristics of hazelnut protein hydrolysates were evaluated. Trypsin, chymotrypsin and thermolysin hydrolysates of hazelnut protein isolates were fractionated using Fast Protein Liquid Chromatography (FPLC). The hydrolysate fractions were tested for ACE inhibitory characteristics and inhibitor peptide identification was based on Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry (LC-Q-TOF/MS). Finally, in vitro ACE inhibitory activity was verified using in silico tools. In all cases, some hydrolysate fractions demonstrated ACE inhibitory characteristics, while inhibitory activity widely varied (7-95%) depending on proteolysis conditions. In ACE inhibitory fractions, 179 different peptides were identified. Their potential inhibitory activity was verified in silico for 22 different peptides generated by thermolysin, 3 for chymotrypsin and 4 for trypsin. While the half maximal inhibitory concentration (IC50) (0.13-4.83 mg ml(-1)) values were comparable to the previous literature, currently identified sequences were different than ACE inhibitory peptides purified from Asian hazelnuts. The peptides with the highest PeptideRanker scores for each treatment (i.e., SPLAGR, VPHW and PGHF) were studied for their potential ACE binding, Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) and circulatory half-life characteristics demonstrating limited pharmokinetic interference, low toxicity as well as comparable short circulation and stronger binding compared to a reference inhibitor peptide (i.e., VPP). Geographical attributes and proteolytic treatments could have a bearing on ACE inhibitory potential of peptides, while hazelnut cakes can be regarded as a valuable resource for ACE inhibitor peptides.
Keywords: Hazelnut protein hydrolysates; Hydrolysate fractions; Valorization; LC-Q-TOF; MS; Angiotensin-converting enzyme (ACE) inhibitory activity; Bioactive peptides